Clinacanthus nutans (Burm.f.) Lindau facilitates cuproptosis and ameliorates colon cancer progression by inhibiting PDE3B-mediated Apelin pathway - Zhou, Gaoyun; Lin, Xueying; Lai, Zhiheng; Su, Dewen; Lin, Long; Chen, Xuewu (Discover. Oncology, 2025)
Background Colon cancer, a prevalent malignancy occurs in the gastrointestinal tract with annually increasing incidence and mortality, and Clinacanthus nutans (Burm.f.) Lindau (CN) possesses anticancer activity in a wide spectrum of tumors. This investigation aims at illuminating potential anti-cancer properties and related mechanisms of CN against colon cancer. Methods A BALB/c mice model of colon cancer administered CN to the experimental group was constructed, followed by transcriptome sequencing on tumor tissues and screening out cuproptosis-related differentially expressed genes (DEGs) through bioinformatics. The anti-tumor efficacy of CN was validated in HT29 and HCT116 cells co-treatment of CN and drug serum by functional assays and therapeutic effects on tumorigenicity were also evaluated in vivo. In addition, the impact of PDE3B silencing on cuproptosis was elucidated and the Apelin pathway activator, CMF-019, was applied to further verify the role of PDE3B on the Apelin pathway in CN-treated cells. Results CN restricted tumorigenesis of colon cancer in vivo. A total of 6 cuproptosis-related DEGs were discovered containing decreased 4 genes and elevated 2 genes in tissues from tumor mice with or without high dose CN treatment. PDE3B deficiency exerted intensified inhibitory effects of CN treatment on proliferative, migratory, and invasive capability, as well as further facilitated cuproptosis. Moreover, PDE3B deletion enhanced the suppression of CN in delaying tumorigenesis. Additionally, CN retarded the malignant phenotypes and contributed to the initiation of cuproptosis in cells via the PDE3B-mediated Apelin pathway. Conclusion Our study revealed CN delayed colon cancer by regulating PDE3B via suppression of the Apelin pathway, indicating the potential clinical relevance of CN in treating colon cancer. Highlights CN exerts anti-tumor effect in colon cancer. CN delays tumorigenesis through suppressing PDE3B. PDE3B silencing enhances cuproptosis in CN-treated cells. CN attenuates colon cancer by modulating PDE3B through via the Apelin pathway.